New combinations and a new generic synonym in the genus Taeniothrips (Thysanoptera: Thripidae) - Mirab-Balou, Majid; Mound, Laurence A.; Tong, Xiao-Li (Zootaxa, 2015)
Reasons are provided for considering Javathrips as a new synonym of Taeniothrips, resulting in the following new combinations: Taeniothrips ciliaris (Reyes) comb.n., Taeniothrips musae (Zhang & Tong) comb.n., and Taeniothrips variegatus (Reyes) comb.n. Also recognised here are the following nomenclatural changes: Taeniothrips grisbrunneus (Feng, Chou & Li) comb.n. (from Megalurothrips), and Yaothrips pediculae Han comb.n. (from Taeniothrips) with Yaothrips shii Mirab-balou et al. syn.n. Taeniothrips musae is redescribed and illustrated.